The Prevalence of Orthostatic Hypotension: A Systematic Review and Meta-Analysis. (29th August 2018) - Saedon, Nor I'zzati; Pin Tan, Maw; Frith, James
Abstract: Background: Orthostatic hypotension (OH) is associated with increased risk of falls, cognitive impairment and death, as well as a reduced quality of life. Although it is presumed to be common in older people, estimates of its prevalence vary widely. This study aims to address this by pooling the results of epidemiological studies. Methods: MEDLINE, EMBASE, PubMed, Web of Science, and ProQuest were searched. Studies were included if participants were more than 60 years, were set within the community or within long-term care and diagnosis was based on a postural drop in systolic blood pressure (BP) ≥20 mmHg or diastolic BP ≥10 mmHg. Data were extracted independently by two reviewers. Random and quality effects models were used for pooled analysis. Results: Of 23, 090 identified records, 20 studies were included for community-dwelling older people ( n = 24, 967) and six were included for older people in long-term settings ( n = 2, 694). There was substantial variation in methods used to identify OH with differing supine rest duration, frequency and timing of standing BP, measurement device, use of standing and tilt-tables and interpretation of the diagnostic drop in BP. The pooled prevalence of OH in community-dwelling older people was 22.2% (95% CI = 17, 28) and 23.9% (95% CI = 18.2, 30.1) in long-term settings. There was significant heterogeneity in both pooled results ( I 2 > 90%). Conclusions: OH is very common, affecting one in five community-dwelling older people and almost one in four older people in long-term care. There is great variability in methods used to identify OH.